100 år med Danmarks Stednavne: – og et kig ind i fremtiden - Eggert, Birgit; Jakobsen, Johnny G.G.; Olesen, Rikke Steenholt (Danske Studier, 2023)
Names are an important part of the intangible cultural heritage that our language represents and placenames are an important source for many subjects such as language research, geography, history, archaeology etc. Therefore, it is an important task to provide knowledge about place-names in a form that can be used widely. This knowledge can be found in the book series Danmarks Stednavne (‘Place-Names of Denmark’), and in 2022, it is one hundred years since the first volume of the series was published. In this article, we present the editorial history of the series and describe the process in the development of the volumes, each standing on the shoulders of its predecessors. The series’ chosen form of production based on a land-registration system, which today can be considered obsolete, is explained, along with the variation regarding which classes of place-names have been treated in each volume and the varying inclusion of settlement-historical presentations based on the place-name evidence. While such issues have changed, the series has upheld a consistent focus on listing historical forms of the place-names and interpreting their etymology. The presentation of the publishing process and changed editorial principles in the course of time are rounded off with the current editorial plans for the future of Danmarks Stednavne.